Penguatan Kapasitas UMKM Kuliner Melalui Teknologi Retort dan Pemasaran Digital: Strategi Pemberdayaan Desa Wisata Mulyaharja Menuju Pariwisata Kuliner Berkelanjutan - Wawan Irawan Saputra; Hendro Soejadi; Mochamad Thariq Yafi Soejadi; Art Dito Pangestu; Suci Sandi Wachyuni; Marya Yenny; Galuh Setyani Putri (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
Mulyaharja Tourism Village in Bogor has strong potential to be developed as a local culinary tourism destination due to its rich organic food resources and traditional products, such as instant nasi liwet, banana blossom pepes, bottled chili paste, cassava chips, and herbal beverages. However, these products face challenges related to shelf life, hygiene standards, branding, and marketing. Local gastronomy is vital for strengthening destination identity, yet it requires packaging innovations and modern promotional strategies.This community service program was designed to enhance the competitiveness of local culinary products through the introduction of retort packaging technology and digital marketing training. Retort technology extends product shelf life without preservatives while maintaining flavor and nutrition. At the same time, digital marketing aligned with Marketing 4.0 enables direct consumer interaction and strengthens MSME branding.The results show that participants improved their understanding of modern packaging and gained practical skills in using social media for product promotion. This program demonstrates that the integration of food technology and digital marketing can empower rural communities, enhance culinary competitiveness, and support Mulyaharja’s development as a sustainable culinary tourism destination